Assessing the efficacy of surgical mask-based modified conventional filtration chambers in eradicating harmful microorganisms from wastewater - Naher, Sabikun; Das, Era Juliet; Toha, Mohammad; Bhuiyan, Md. Arifur Rahman; Tania, Khadiza Akter (Urban water journal, 2024)
Subsequent to the COVID-19 pandemic, waste management posed escalating challenges attributed to the imprudent disposal of medical waste, notably surgical masks. Hence, the present investigation was undertaken concomitantly to confront the dual concerns of mitigating environmental pollution and managing discarded face masks. The experimental methodology entailed the utilization of filtration chambers featuring surgical mask layers of distinct thicknesses, labeled as Treatment-0 (no mask layer), Treatment-1 (5 mm mask layer), Treatment-2 (10 mm mask layer), and Treatment-3 (15 mm mask layer), to eliminate pathogenic microorganisms from contaminated river water, Buriganga. At the end of the observation, Treatment-3 exhibited the most significant declination (88.15%) of the bacterial population. This treatment also removed most pathogens, including E. Coli (19.85%), total coliform (16.42%), and fecal coliform (12.02%). The findings underscore the significance of modern filtration systems and the efficient, ecologically viable recycling of medical waste, with a specific focus on surgical masks.